Paulo Freire, filósofo, pedagogo e cientista social: Singularidade e a universalidade do seu pensamento - José Rubens L. Jardilino (Universidad Pedagógica y Tecnológica de Colombia, 2008)
This paper deals with a summary of the ideas of the small book stated by the author, beginning within the filing of the Freire is thought. This version comes in Portuguese, it deals with the biographic remnants of life span and the thought of the educator Paulo Freire. We also invite the readers of the Rhela to keep a record about life span and thought of the emblematic educator Pablo Nun, who died ten years ago.